One piece. Baroque Works. Vol. 16, Carrying on his will - Oda, Eiichiro, 1975-; Caselman, Lance; JN Productions (San Francisco, CA : VIZ Media, LLC, 2007)
Luffy must determine whom to trust when King Wapol orders his and Sanji's deaths and a rescue comes from an unlikely source.
"First published in Japan in 1997 by Shueisha Inc, Tokyo"--Page facing t.p.
"Parental advisory. One Piece is rated T for teen and is recommended for ages 13 and up. This v. contains fantasy violence and tobacco usage"--Page facing t.p.
"This book reads from right to left"--Back cover.
"This v. contains material that was originally published in English in Shonen Jump #56-58"--Page facing t.p.
Translated from the Japanese.
Adult
Keywords: Pirates -- Comic books, strips, etc. -- Fiction; Treasure troves -- Comic books, strips, etc. -- Fiction; Buried treasure -- Comic books, strips, etc. -- Fiction; Manga; Pirates -- Comic books, strips, etc. -- Fiction; Action and adventure comics; Graphic novels